(untitled) (INGE@UAN - TENDENCIAS EN LA INGENIERÍA, 2013)
This paper describes the development of an algorithm of artificial vision, which uses the color space conversion RGB of the image of the human face, to the color space YCbCr. Through analysis of histogram of Cr component, is achieved the calculation of an apropiated treshold for the tresholding and segmentation of the lip region. The obtained results have an efficiency of 91% under controlled conditions of lighting.